Training on Augmented Reality Applications for Teachers as an Online Learning Medium - Nasrulloh, Iman; Abdurahman, Luki; Surya, Andri Permata; Saepurrohman, Saepurrohman Permata (Fakultas Kewirausahaan Universitas Garut, 2022)
This community service program aimed to enhance teachers' competencies in utilizing Augmented Reality (AR) applications as innovative learning media during online teaching. The training introduced teachers to accessible AR applications such as Quiver, Assemblr, and Merge Cube, accompanied by direct practice sessions to improve their technical and creative skills in designing interactive learning materials. A descriptive approach was used to evaluate the effectiveness of the program by collecting participants' feedback before and after training. The results showed that teachers demonstrated improved understanding and confidence in applying AR as a teaching tool, with positive impacts on their ability to design engaging and interactive lessons. Despite challenges such as limited digital literacy and unstable internet connectivity, participants were able to overcome these issues through mentoring and peer discussions. This program highlights the potential of AR to improve the quality of online learning and underlines the importance of continuous support and digital infrastructure in sustaining its implementation.